Ultrasonication effects on graphene composites in neural cell cultures - Dybowska-Sarapuk, Łucja; Sosnowicz, Weronika; Grzeczkowicz, Anna; Krzemiński, Jakub; Jakubowska, Małgorzata (Frontiers in Molecular Neuroscience, 2022)
Spinal cord injuries and neurodegenerative diseases, including Parkinson’s, Alzheimer’s, and traumatic brain injuries, remain challenging to treat. Nowadays, neural stem cell therapies excite high expectations within academia. The increasing demand for innovative solutions in regenerative medicine has drawn considerable attention to graphene materials. Due to unique properties, carbon materials are increasingly used as cellular scaffolds. They provide a biological microenvironment supporting cell adhesion and proliferation. The topography and mechanical properties of the graphene culture surface influence the forces exerted by the cells on their extracellular matrix. Which consequently affects the cell proliferation and differentiation. As a result, material properties such as stiffness, elasticity and mechanical strength play an important role in stem cells’ growth and life. The ink unification process is crucial while the layer homogeneity is essential for obtaining suitable surface for specific cell growth. Different ink unification processes were tested to achieve appropriate layer homogeneity and resistivity to successfully applied the GNPs layers in neural cell electrostimulation. The GNP coatings were then used to electrostimulate mouse NE-4C neural stem cells. In this study, the authors investigated how the stimulation voltage amplitude’s value affects cell behaviour, particularly the number of cells. Sinusoidal alternating current was used for stimulation. Three different values of stimulation voltage amplitude were investigated: 5, 10, and 15 V. It was noticed that a lower stimulation voltage amplitude had the most favourable effect on the stem cell count.